2021
DOI: 10.3389/fpls.2020.614360
|View full text |Cite
|
Sign up to set email alerts
|

Time Lag Between Light and Heat Diurnal Cycles Modulates CIRCADIAN CLOCK ASSOCIATION 1 Rhythm and Growth in Arabidopsis thaliana

Abstract: Plant growth responses to cues such as light, temperature, and humidity enable the entrainment of the circadian rhythms with diurnal cycles. For example, the temperature variations between day and night affect plant growth and accompany the time lag to light cycle. Despite its importance, there has been no systematic investigation into time lags, and the mechanisms behind the entrainment of the circadian rhythms with multiple cycles remain unknown. Here, we investigated systemically the effects of the time lag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 27 publications
(19 reference statements)
1
9
0
Order By: Relevance
“…The interaction between time of day and temperature signaling can also influence clock function. In Arabidopsis grown under LD conditions, a 4-h temperature cycle of ±10°C given at different times of day causes unique effects on the oscillator ( Masuda et al, 2020 ). A 10°C increase had a more dramatic effect on CCA1 promoter expression that was time of day dependent compared to a 10°C drop, which had minimal effects overall.…”
Section: Role Of the Clock In Temperature Perception And Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between time of day and temperature signaling can also influence clock function. In Arabidopsis grown under LD conditions, a 4-h temperature cycle of ±10°C given at different times of day causes unique effects on the oscillator ( Masuda et al, 2020 ). A 10°C increase had a more dramatic effect on CCA1 promoter expression that was time of day dependent compared to a 10°C drop, which had minimal effects overall.…”
Section: Role Of the Clock In Temperature Perception And Signalingmentioning
confidence: 99%
“…A 10°C increase had a more dramatic effect on CCA1 promoter expression that was time of day dependent compared to a 10°C drop, which had minimal effects overall. The 10°C increase was associated with greater fresh weight when given at 8 h compared to 14 h after dawn, with a linear relationship between CCA1 amplitude and growth ( Masuda et al, 2020 ). This response may be tuned to the expectation that the warmest part of the day usually occurs in the mid-afternoon rather than near dusk ( Figure 1 ).…”
Section: Role Of the Clock In Temperature Perception And Signalingmentioning
confidence: 99%
“…This acceleration of plant development has been proposed as an effect of the modification of the circadian clock [24]; some of the signals regulating this mechanism include light and temperature and are associated with the compensation of plant growth in seasonal changes [25]. A study in A. thaliana reported that circadian modifications and their physiological effects, such as an accelerated change to the reproductive stage, are more significant in the increase in temperature than in the decrease [26].…”
Section: Acceleration Of Developmentmentioning
confidence: 99%
“…Circadian clock comprises multiple transcription-translation feedback loops, which function to improve plant environmental adaptation. Altered expression of circadian clock genes, such as CIRCADIAN CLOCK ASSOCIATED1 ( CCA1 ), can increase levels of plant growth and fitness ( Dodd et al, 2005 ; Masuda et al, 2020 ). Meanwhile, expression amplitude of CCA1 is associated with the CHH methylation level in the promoter region, which determines plant growth vigor ( Ng et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%